JKN FUND MANAGEMENT IN FULFILLMENT OF HEALTH PERSONNEL SERVICES IN PUSKESMAS BONGO II WONOSARI DISTRICT - Linda Ali; Imam Mashudi; Siske Anani (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine the management of JKN funds in fulfilling theservices of health workers at the Bongo II Health Center, Wonosari District.The method in this study uses descriptive qualitative methods with datacollection and observation techniques, in-depth interviews and documentation withSWOT data analysis.The results of this study indicate that the management of JKN funds at theBongo II Health Center must be even better, so that the implementation of theprogram will run well and regularly.The advantage of the Bongo II Health Center is that it has implemented orimplemented the JKN fund program. The weakness that must be corrected is that inplanning the making of the work program it must be in accordance with the existingconditions at the Bongo II Health Center and the knowledge possessed by theexisting officers. As well as officers who work at the Bongo II Health Center musthave knowledge in accordance with what is their main task or even have completedthe level of education in accordance with their field of work, so that in carrying outthe work there will be no difficulties.